Peran Teknologi Digital dalam Strategi Orang Tua Menanamkan Pendidikan Agama Islam pada Generasi Z - Sani, Mutiara; Fatimah, Meti; Subando, Joko (Lembaga Yasin AlSys, 2026)
The rapid development of digital technology has significantly transformed family education patterns, particularly in the provision of Islamic religious education for Generation Z, who are growing up as digital natives, such that intensive exposure to digital media presents both opportunities and challenges for parents in shaping their children’s religious character. This article aimed to analyze the role of digital technology in parents’ strategies for instilling Islamic religious education in Generation Z through a literature-based study. The research employed a qualitative approach with a library research method, drawing on data sources that included scholarly books, reputable national and international journal articles, and relevant research reports. Data were collected through documentation techniques and analyzed using content analysis and thematic analysis, while data validity was maintained through source and theoretical triangulation. The findings indicate that digital technology plays a strategic role in family-based Islamic religious education when it is used in a purposeful and well-supervised manner, with identified parental strategy models including role modelling in digital media use, supervision and guidance, dialogical-educative approaches, and integrative strategies that combine conventional Islamic educational practices with the use of digital media. The main challenges arise from parents’ limited digital literacy and children’s exposure to digital content that conflicts with Islamic values, whereas the opportunities lie in broad access to innovative and contextually relevant Islamic digital resources. This study concludes that the effectiveness of Islamic religious education for Generation Z in the digital era largely depends on parents’ ability to mediate technology use in an educational and value-oriented way, so that technology serves not only as a means of entertainment but also as a vehicle for strengthening faith and shaping children’s religious character.